Prison libraries in Turkey: The results of a national survey - Dilek-Kayaoglu, Hülya; Demir, Güler (SAGE Publications, 2014)
The purpose of this study is two-fold: first, to examine the historical development of prison libraries in Turkey in the context of relevant legislation; and second, to determine the current state of prison library services in Turkey on the basis of the results of a survey which was conducted throughout the country between January and April 2011. There are regulations, without the force of law, which provide for the establishment, management, and control of libraries in correctional facilities and there is a uniform organizational structure countrywide. However, the 2011 survey showed that, in practice, prison libraries are unsuccessful in providing a professional service.
Keywords: 16. Peace & justice